2018
DOI: 10.1186/s12885-018-4500-9
|View full text |Cite
|
Sign up to set email alerts
|

The PDGFRβ/ERK1/2 pathway regulates CDCP1 expression in triple-negative breast cancer

Abstract: BackgroundCDCP1, a transmembrane protein with tumor pro-metastatic activity, was recently identified as a prognostic marker in TNBC, the most aggressive breast cancer subtype still lacking an effective molecular targeted therapy. The mechanisms driving CDCP1 over-expression are not fully understood, although several stimuli derived from tumor microenvironment, such as factors present in Wound Healing Fluids (WHFs), reportedly increase CDCP1 levels.MethodsThe expression of CDCP1, PDGFRβ and ERK1/2cell was teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…For instance, TNBC patients frequently harbour higher expression of EGFR; however, studies have failed to establish significant benefit from EGFRtargeted therapies or tyrosine kinase inhibitors, suggesting the need to therapeutically target other pathways in these tumors 38,39 . Moreover, the significance and over-activation of pathways such as; P38 MAPK , the PDGF, and the RAS pathways in BC metastatic sites and their association with DMFS and BCSS in TNBC have been previously documented [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TNBC patients frequently harbour higher expression of EGFR; however, studies have failed to establish significant benefit from EGFRtargeted therapies or tyrosine kinase inhibitors, suggesting the need to therapeutically target other pathways in these tumors 38,39 . Moreover, the significance and over-activation of pathways such as; P38 MAPK , the PDGF, and the RAS pathways in BC metastatic sites and their association with DMFS and BCSS in TNBC have been previously documented [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ERK1/2 is a well‐known kinase that can be phosphorylated by many cytokines. It is closely related to tumour growth and metastasis . The activation of ERK promotes proliferation and metastasis of gallbladder cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we have established that growth factors that are released during wound healing following surgery account for the early relapse of the HER2-positive breast cancer subtype [17,18]. Moreover, we recently demonstrated that exposure of triple-negative (TN) breast cancer cells to WHF in vitro increases their expression of CDCP1, a molecule that is associated with a poor prognosis in several types of tumor, including TNBC [19,20].…”
Section: Introductionmentioning
confidence: 99%